Clean-Nutrition, Care-Green Marketing, Commit-Loyalty Program: 3C Strategy as a Driver of Customer Satisfaction and Loyalty - Rindang Nirmala Trisnaningsih; Tanto Gatot Sumarsono; Umu Khouroh (Jurnal Bisnis dan Manajemen, 2025)
This study investigates the effects of the 3C Strategy—Clean–Nutrition, Care–Green Marketing, and Commit–Loyalty Program—on customer satisfaction and loyalty in the mass-affordable dairy sector in Indonesia. It also examines the mediating role of customer satisfaction in translating marketing strategies into long-term loyalty, particularly among Bottom-of-the-Pyramid (BoP) consumers. Using an explanatory quantitative approach, the study surveyed 210 respondents from urban and semi-urban areas who had recently purchased affordable dairy products and met age and expenditure criteria. Data were collected through structured questionnaires and analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The results reveal that all three strategic elements significantly influence both satisfaction and loyalty, with Care–Green Marketing having the strongest direct effect on customer loyalty. Clean–Nutrition contributes primarily to satisfaction, while Commit–Loyalty Program shows dual effects by enhancing both satisfaction and loyalty directly. Mediation analysis confirms that satisfaction significantly bridges the relationship between the 3C elements and loyalty outcomes. These findings suggest that consumer decisions in low-income markets are not solely driven by price but are increasingly shaped by ethical values, health consciousness, and relational benefits. The results also validate the applicability of Expectation–Confirmation Theory and the Stimulus–Organism–Response framework in the context of functional FMCG products for BoP consumers. The study offers theoretical contributions by integrating ecological and ethical dimensions into consumer value frameworks and provides practical insights for marketers seeking to foster enduring customer relationships through transparent, value-based branding strategies.